Post-partum cutaneous manifestation of antiphospholipid syndrome - Yumeng Zhang; Nicole D. Riddle; Lucia Seminario-Vidal (Elsevier, 2019)
Antiphospholipid syndrome is a systemic autoimmune disease defined by thrombotic or obstetrical events that occur in patients with persistent antiphospholipid antibodies. The most common dermatologic presentation is livedo reticularis. However, other cutaneous manifestation can also be present. We describe a female patient that postpartum developed diffuse and rapidly progressing retiform purpura to highlight this atypical presentation noted after delivery. The diagnosis is complicated by the presence of vasculitis with fibrin thrombi in the skin biopsy in the absence of systemic vasculitis. This is of interest because vasculitis is a rare manifestation in antiphospholipid syndrome alone. Keywords: Retiform Purpura, Antiphospholipid syndrome, Post-partum